2017
DOI: 10.1590/1413-785220172503167325
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in brazilian patients awaiting knee arthroplasty

Abstract: OBJECTIVE: The primary objective of this study was to determine the prevalence of osteoporosis and osteopenia prior to total knee arthroplasty (TKA) in female patients. As a secondary objective, we evaluated the incidence of hip fractures, types of drugs to treat osteoporosis and serum vitamin D levels. METHOD: This is a transversal, descriptive and observational study which evaluated 60 women above age 55 prior to total knee replacement. RESULTS: Mean patient age was 71.4 years. Osteoporosis was present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…L ow bone mineral density (BMD) appears to be common in patients undergoing total joint replacement (TJR), with up to two thirds and one third meeting criteria for osteopenia and osteoporosis, respectively. [1][2][3][4][5][6][7][8][9] Emerging data raise concerns that low BMD may increase the risk of intraoperative and postoperative complications in patients undergoing TJR. In a study of total ankle arthroplasty, low tibial BMD, as measured by Hounsfield units, from preoperative ankle computed tomography scan was associated with a higher risk for periprosthetic fracture (P=.018), with all intraoperative fractures occurring in patients with tibial Hounsfield units less than 200.…”
mentioning
confidence: 99%
“…L ow bone mineral density (BMD) appears to be common in patients undergoing total joint replacement (TJR), with up to two thirds and one third meeting criteria for osteopenia and osteoporosis, respectively. [1][2][3][4][5][6][7][8][9] Emerging data raise concerns that low BMD may increase the risk of intraoperative and postoperative complications in patients undergoing TJR. In a study of total ankle arthroplasty, low tibial BMD, as measured by Hounsfield units, from preoperative ankle computed tomography scan was associated with a higher risk for periprosthetic fracture (P=.018), with all intraoperative fractures occurring in patients with tibial Hounsfield units less than 200.…”
mentioning
confidence: 99%
“…Several studies have reported the incidence of OP before TKA. In the non-Asian population, 9.6-33% of TKA candidates have been found to suffer from OP, regardless of the patient's sex, 16,[27][28][29][30] and 35% of women awaiting TKA or total hip arthroplasty have been found to have OP. 15 In contrast, two Korean studies have reported OP incidence rates of 40.1 and 53.4% among women indicated for TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a positive correlation between the severity of OA and the level of bone mineral density (BMD) and that OA is a protective factor against OP, [12][13][14] while several researchers have instead suggested that OP exists in a considerable number of patients with advanced OA. 15,16 Dual-energy X-ray absorptiometry (DXA) scans of at least two bone sites are recommended by the International Society for Clinical Densitometry (ISCD) to diagnose osteoporosis based on the T-score. However, some studies have shown that the BMD region of interest (ROI) may be affected by orthopaedic diseases, thus resulting in the BMD not being correlated with OP and inconsistent diagnoses between different sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, newer studies on the association between osteoarthritis and osteoporosis with subsequent fracture risk show conflicting results [21,22]. While some studies show a low prevalence of osteoporosis and increased bone mass in patients with osteoarthritis undergoing TKR/THR [13,22,23], others show a prevalence roughly equal to that in the general population [12,24], while yet others show an increased risk of fractures in these patients [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite several international studies reporting the prevalence of osteoporosis in patients undergoing arthroplasty and spinal procedures [13,[22][23][24][44][45][46][47][48], adequate research on osteoporosis prevalence in Indian patients undergoing these procedures is lacking. While several papers have examined implant design in arthroplasty [13,[22][23][24]47,48], relatively fewer have assessed the quality of the underlying bone into which the implants are inserted [13,22].…”
Section: Introductionmentioning
confidence: 99%